1986
DOI: 10.1111/j.1570-7458.1986.tb01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history response of female Mediterranean fruit flies, Ceratitis capitata, to periods of host deprivation

Abstract: Female medflies were subjected to four different patterns of host deprivation at each of three levels for a 24‐day period. Treatments ranged from host absence 8 days post‐eclosion to host absence 2 out of 3 days. Survival was recorded daily and egg production was recorded on the days in which hosts were present. The direct effect of host deprivation is to deny females the opportunity to oviposit. This disrupts their reproductive cycle and reduces their overall reproductive effort. Reduced reproductive effort a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 9 publications
2
28
1
1
Order By: Relevance
“…Carey et al, 1986). An important implicit assumption in these designs is that such deprivation directly causes a reduction in reproduction which leads to increased investment in somatic function.…”
Section: Discussionmentioning
confidence: 93%
“…Carey et al, 1986). An important implicit assumption in these designs is that such deprivation directly causes a reduction in reproduction which leads to increased investment in somatic function.…”
Section: Discussionmentioning
confidence: 93%
“…A substantial body of theoretical and experimental research on the costs of reproduction (Partridge & Farquhar 1981) and on reproductive determinism (Maynard Smith 1958;Minchella & Loverde 1981;Bell 1984;Bell & Koufopanou 1986;Carey et al 1986) has shown that reproduction can decrease survival and that exhaustion of reproductive capacity plays a role in ageing. Our ¢ndings point to a fundamental link between reproductive dynamics and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a polyphagous insect with high behavioral adaptability, as A. obliqua, may keep a large number of hosts. Several authors (Carey et al 1986;Prokopy & Reynolds 1998;Díaz-Fleischer & Aluja 2003a, 2003b) and the present study have reported the plasticity of fruit flies concerning their oviposition behavior strategies. In this sense, further investigations on the factors related to this behavior are needed.…”
Section: Discussionmentioning
confidence: 92%